Discourse Analysis and English Language Teaching - Nurdiana Nurdiana (Universitas Bunda Mulia, 2017)
In the past, English language teaching (ELT) put more emphasis on the teaching of structure of the language. Meaning and contexts seemed to be neglected. However, over the past few years, the trend has changed. Grammar and structure (language forms) are not the single element of language learned in English language learning. Context should be taken into account when teaching and learning a language. In this paper, I shall discuss the relationship between contexts and language teaching, particularly English language teaching. In other words, this paper discussess discourse analysis in regard to ELT. Keywords: discourse analysis, English language teaching